The Distribution of Anacardiaceae in Teluk Bahang Forest Reserve, Pulau Pinang - Shaodah Juperi,; Rahmad Zakaria,; Asyraf Mansor , (Tropical Life Sciences Research, 2012)
To investigate the distribution of Anacardiaceae in Teluk Bahang Permanent Forest Reserve (TBPFR) in Pulau Pinang, all trees with a diameter at breast high (DBH) ? 5 cm were enumerated in a study site constituting 0.4 ha of the reserve. Seventy five individuals of Anacardiaceae (14% of all trees) are recorded. These individuals represent 4 genera and 5 species, namely, Mangifera pentandra, Mangifera macrocarpa, Gluta elegans, Campnosperma auriculatum and Swintonia floribunda. The mean density of Anacardiaceae within the study plots is 7.50±8.14 (mean±S.D.) per ha whereas the basal area (BA) calculated is 0.97 m2/0.40 ha. The importance value (IVi) for Anacardiaceae is 81%. The estimated total aboveground biomass (TAGB) for Anacardiaceae is 24.24 ton/0.40 ha. A total of 333 Anacardiaceae saplings with a DBH < 5 cm are recorded. These saplings have been identified as juveniles of the genera Gluta (9.99%), Swintonia (84.90%) and Mangifera (5.11%). Kajian dijalankan dalam kawasan seluas 0.4 ha di Hutan Simpan Teluk Bahang, Pulau Pinang ke atas pokok berukuran ketinggian paras dada (DBH) ? 5 cm. Tujuh puluh lima individu Anacardiaceae (14% daripada jumlah semua pokok) direkodkan, diwakili oleh 4 genus dan 5 spesies iaitu Mangifera pentandra, Mangifera macrocarpa, Gluta elegans, Campnosperma auriculatum dan Swintonia floribunda. Purata kepadatan Anacardiaceae di dalam plot adalah 7.50±8.14 (min±S.D.) per ha dengan keluasan pangkal 0.97 m2/0.40 ha dan nilai kepentingan (IVi) 81%. Nilai anggaran biojisim atas tanah Anacardiaceae adalah 24.24 tan/0.40 ha. Di samping itu, sejumlah 333 juvenil pokok Anacardiaceae dengan ukuran DBH < 5 cm telah direkodkan dan dikenalpasti daripada genera Gluta (9.99%), Swintonia (84.90%) dan Mangifera (5.11%).